2021
DOI: 10.1111/jcpe.13471
|View full text |Cite
|
Sign up to set email alerts
|

Dental biofilm of symptomatic COVID‐19 patients harbours SARS‐CoV‐2

Abstract: Aims SARS‐CoV‐2 RNA has been recovered from different sites in the human body, including the mouth. The present study aimed to investigate the presence of SARS‐CoV‐2 RNA in the dental biofilm of symptomatic patients who tested positive in nasopharyngeal and oropharyngeal (NASO/ORO) samples. Materials & Methods An observational clinical study of individuals with flu‐like symptoms was conducted between July and September 2020. Dental biofilm (BIO) samples were collected and analysed using real‐time quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 32 publications
1
46
0
1
Order By: Relevance
“…COVID-19 can be transmitted through small droplets of expelled saliva; after inhalation of these droplets, host cells can be infected and symptoms of the disease can appear (J. Xu et al, 2020; R. Xu et al, 2020). SARS-CoV-2 can be found not only in saliva, but also in dental plaque ( Gomes et al, 2021 , To et al, 2020 ). As the saliva and oral cavity are considered reservoirs of the virus, the use of mouthwashes could help in the decrease of COVID-19 transmission.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 can be transmitted through small droplets of expelled saliva; after inhalation of these droplets, host cells can be infected and symptoms of the disease can appear (J. Xu et al, 2020; R. Xu et al, 2020). SARS-CoV-2 can be found not only in saliva, but also in dental plaque ( Gomes et al, 2021 , To et al, 2020 ). As the saliva and oral cavity are considered reservoirs of the virus, the use of mouthwashes could help in the decrease of COVID-19 transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, understanding the sites within the body that could harbor severe acute respiratory syndrome coronavirus 2 is important to prevent and limit its transmission. Using real‐time quantitative PCR, a recent study has reported the presence of severe acute respiratory syndrome coronavirus 2 in dental biofilm 196 . Severe acute respiratory syndrome coronavirus 2 is present in high levels in saliva and persists up to 11–15 days after infection 197 .…”
Section: The Perio‐systemic Connection: Connected By Viruses or By Ba...mentioning
confidence: 99%
“…As discussed previously, the oral cavity can act as a reservoir and point of entry for SARS-CoV-2. SARS-CoV-2 was detected in dental plaque of symptomatic COVID-19 patients [38] and in gingival crevicular fluid and saliva of both asymptomatic and mildly symptomatic COVID patients [39]. These findings should be considered when defining preventive measures to stop the transmission of the SARS-CoV-2 in dental practice.…”
Section: Periodontitis and Covid-19mentioning
confidence: 99%